Lacaziosis: immunohistochemical evaluation of elements of the humoral response in cutaneous lesions - Kanashiro-Galo, Luciane (2020)
Lacaziosis is a cutaneous mycosis caused by the fungus Lacazia loboi, described in different countries of Latin America and prevalent in the Amazon region. The ineffective immune response against the agent seems to be related to a Th2 pattern of cytokines. There are few reports exploring elements of the humoral response in these lesions. Our aim was to investigate some elements focusing on B cells, plasma cells and local expression of IgG and IgM antibodies. Forty skin biopsies of lower limbs were selected. The diagnosis of lacaziosis was based on direct mycological examination and histological analysis. The visualization of fungal cells was improved by using Gridley’s staining. An immunohistochemical protocol was performed to detect the expression of B cells, plasma cells, IgG and IgM. A double staining was performed to explore the presence of yeasts in the cytoplasm of keratinocytes, using an anti-AE1 AE3 antibody over Gridley’s staining. The inflammatory infiltrate consisted of macrophages, multinucleated giant cells, lymphocytes, and fibrosis. Fungal cells were frequent in the stratum corneum and in both, the dermis and, in 50% of the specimens, also in the epidermis. Cells expressing IgG were more abundant when compared to cells expressing IgM. B cells and the presence of IgG might indicate that the humoral response promotes a Th2 immune response resulting in an anti-inflammatory phenotype. Our results lead us to suggest a possible role of B cells and immunoglobulins in the mechanisms of lacaziosis pathogenesis.